Prospective long-term follow-up of patients with localised Wegener's granulomatosis: does it occur as persistent disease stage?. Issue 11 (28th May 2010) - Holle, Julia U; Gross, Wolfgang L; Holl-Ulrich, Konstanze; Ambrosch, Petra; Noelle, Bernhard; Both, Marcus; Csernok, Elena; Moosig, Frank; Schinke, Susanne; Reinhold-Keller, Eva
Abstract : Objective: To identify patients with localised Wegener's granulomatosis (locWG) to assess whether it occurs as a long-term disease stage or phenotype and to characterise its outcome. Methods: Patients in a 'localised stage' with histological criteria compatible with WG and a follow-up period of ≥1 year were included. They were prospectively followed at the Vasculitis Center Schleswig-Holstein from 1989 to 2009 and the clinical manifestations, antineutrophil cytoplasmic autoantibodies (ANCA) status and damage were evaluated. Immunosuppression was adapted to disease activity and severity in a step-up regimen. Results: Of 1024 patients with suspected WG, 99 were clinically diagnosed with locWG and 50 fulfilled the inclusion criteria (72% women, median age 43 years, 46% ANCA-positive). The median follow-up was 48 months. All achieved a response to treatment, 34% achieved complete remission, 1–4 relapses occurred in 46%, 5 (10%) had generalised disease (median 6 years after onset). ANCA status was not associated with relapse (p=0.98), transition to generalised disease (p=0.51) or refractory manifestations (p=0.60). 47% required cyclophosphamide for localised manifestations, 36% of them for pulmonary masses and 24% for orbital masses. 66% developed organ damage, mostly due to bony destruction or space obturation (28% saddle nose, 24% septal perforation, 10% orbital wall destruction). There were two deaths that were not related to WG. Conclusion: There is evidence that locWG is a long-term disease stage or phenotype (5% of all patients with WG), 46% of whom are ANCA-positive. LocWG is characterised by destructive and/or space-consuming lesions associated with high relapse rates (46%) and local damage.